Global Mental Health: An Introduction. Issue 8 (17th August 2016) - Verdeli, Helen
Abstract : In this introductory paper to the Global Mental Health volume, the inception and development of the filed in the last 15 years is reviewed, placing an emphasis on a series of pivotal turning points. A critical delivery strategy, task‐shifting is briefly described, as well as the fundamental principles of Interpersonal Psychotherapy (IPT), an evidence‐based psychotherapy being adapted and delivered in low‐resource settings. Nine case studies by the trainees, supervisors, or local providers from India, the United States, Haiti, Israel, Colombia, and Kenya, presented in this volume, illustrate the prevention and treatment processes or in‐depth assessment of "psychological distress" as locally defined and expressed.